Cultivation of microalgae spirulina sp. in palm oil mill effluent for essential fatty acids production - Palanisamy, Karthick Murugan (2021)
Essential fatty acids providing health benefits and has increased the consumption as dietary supplements. Omega-3 fatty acids, usually derived from fatty fish, are present in animals, transgenic plants, fungi and many microorganisms, bringing excessive pressure on global fish stocks. Fortunately, microalgae are the primary which are rich in essential fatty acid and present a promising source of omega-3 fatty acid. The cost of nutrient media becomes an obstacle for cultivation of microalgae in larger industry. In this study, total 16 indigenous microalgae been identified and six monoculture of different species such as Amphora sp., Anabaena sp., Chlorella sp., Scenedesmus sp., Spirulina sp., and Tetraselmis sp., were isolated in laboratory environment by using serial dilution and streaking plate techniques from the marine sample collected East costal region of Kuantan, Pahang. These species were tested the growth and survivability in mixture of 5% (v/v) POME + conventional medium. Among these, Spirulina sp. shown higher growth and higher survivability while evaluating and chosen for further experiment. The growth of Spirulina sp. was tested by feeding POME as an only medium with different concentration (10-50% v/v) to maximize the biomass production. Followed with different effect of light intensities (1000-4000 lux) and temperature (21-36±2 ℃). The growth rate of Spirulina sp. was measured by biomass concentration (mg/L) and Chlorophyl content (µg/mL). The highest biomass production of Spirulina sp. was found in the optimum conditions of 30% v/v of POME, 3000 lux light intensity and 31±2 ℃ temperature with highest biomass yield 1.54±0.11 g/L after 18 days of cultivation. The biomass of Spirulina sp. was separated from the culture medium by centrifugation at 6000 g and dried at 70±3 ℃. Dried biomass was treated with hexane and extracted the highest lipid from Soxhlet extractor (44.9±6.1%) as compared to ultrasound assisted (32.3±6.5%) and Bligh and Dyer method (12.3±4.0%). The extracted lipids were trans esterified using methanolic KOH (1:1 v/v) for 120 min at 60±2℃ with aim of obtaining fatty acid methyl ester. Fatty acid methyl ester sample added with internal standard heptadecanoic acid which diluted with octane at 15 mg/ml. 1 µL of samples were analyzed using gas chromatography. Among 13 fatty acids found that, oleic acid (70.16%), palmitoleic acid (13.07%), linoleic acid (8.62%), and stearic acid (2.11%) and ℽ-linolenic acid (0.43%) as dominant fatty acids. Spirulina sp. lipid have great potential to be use in nutraceutical and pharmaceutical product due to its composition of essential fatty acids.